GB Virus C Infection: Clinical Significance. (1st December 1999) - Meng, Xiang Wei; Komatsu, Masafumi; Ohshima, Shigetoshi; Nakane, Kunio; Fujii, Tomoo; Goto, Takashi; Yoneyama, Kazuo; Kuramitsu, Tomoyuki; Mukaide, Motokazu
Abstract : GB virus C (GBV-C) RNA positivity rates were examined in serum specimens from 231 patients with liver disease (23 patients with hepatitis B, 175 patients with hepatitis C, five patients with hepatitis B virus plus hepatitis C virus coinfection, and 28 patients with non-A, non-B, non-C hepatitis) to clarify the clinical significance of this virus. GBV-C RNA was detected in none of 12 patients with fulminant hepatitis, one of two patients with acute hepatitis positive for hepatitis B surface antigen and one of four patients with acute non-A, non-B, non-C hepatitis. Pathogenetic involvement of GBV-C was suspected in some patients in the latter group. Among patients with the non-B, non-C type of chronic disease, one of seven with cirrhosis (14%) and none with chronic hepatitis or hepatocellular carcinoma were GBV-C-positive. In chronic hepatitis C patients who had received interferon treatment, no difference was found in clinical findings, alanine aminotransferase (ALT) concentrations, histology or response to interferon between 11 patients who were GBV-C RNA-positive and 101 patients who were GBV-C RNA-negative. Moreover, changes in ALT after interferon therapy showed no relation to positivity for GBV-C RNA. On the basis of these findings, GBV-C appears to be an unlikely cause of initiation or progression of chronic hepatic diseases.